Performance Evaluation of Organic Anti-Corrosion Coating for Car Based on Electrochemistry - SU Jian, CONG Yu-feng, HUANG Wei, JIANG Chuan-dong (Cailiao Baohu)
In order to deal with the corrosion problem of car cavity, an anti-corrosion organic coating for the inner cavity of a car was prepared to protect the inner cavity during corrosion during service.The performance of coatings was evaluated by high/low temperature test, thermal analysis, microstructure, wet heat test, salt spray test and electrochemical test.Results showed that the coating had good stability in high temperature(80 ℃, 24 h)and low temperature(-35 ℃, 8 h), and the film structure was compact.After 360 h under the conditions of high temperature and high humidity, and 120 h in salt spray environment, the corrosion resistance reached the industry standard level one.After immersed in 3.5%(mass fraction)NaCl solution for 96 h, the coating resistance still reached 3.14×106 Ω·cm2, indicating that the organic anti-corrosion coating had good anti-corrosion performance.